Implementasi Sertifikasi Halal pada Pedagang Sate di Kecamatan Deli Tua Perspektif UU No. 33 Tahun 2014 Tentang Jaminan Produk Halal - Isnaina Rizkia Ritonga; Abd. Rahman Harahap (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
Halal product assurance for satay businesses in Deli Tua District does not meet legally mandated standards. This study examines the implementation of halal certification among satay vendors in Deli Tua District based on Law Number 33 of 2014 concerning Halal Product Assurance, focusing on the gap between normative provisions and field conditions. The method used is empirical juridical with a sociological approach through observation, interviews, and document studies. The results indicate that the implementation of halal certification remains low, with most businesses not yet certified despite understanding its importance, creating a gap between regulations and practice. The main obstacles include the perception of small businesses that have not prioritized certification, a lack of technical understanding of halal certification procedures, and minimal government outreach and assistance. Satay vendors need to increase their initiative in managing halal certification to optimize its implementation and strengthen public trust in their products.